Pesantren and Surau as Forms of Modern Islamic Education Traditions in Indonesia - Heni Yuliana Wati; Rina Mida Hayati; Dika Tripitasari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
Pesantren is a historical tradition of Islamic education in Indonesia which originated from ancient times and it has been proven that in addition to educating about the faith and piety of the students (santri) and also educating about noble character. Surau is a place for traditional ceremonies and then gradually becomes a place of worship and as a gathering place for young people to learn to explore skills and various knowledges. Surau and Islamic boarding schools in Indonesia must be maintained and developed for their existence as one of the institutions whose presence is in the middle of the life of the wider community. After being able to fight the invaders and then Indonesia became independent, the pesantren that had been established filled independence with things that were full of benefits without having to be afraid of the invaders. The tradition and modernization of Islamic education in Indonesia is not just a boarding school, but there are also mosques, madrasas and halls.